A Historical Perspective Study of Yakthung Mangena Mundhum - Yongya , Birman (HISAN: Journal of History Association of Nepal, 2024)
This study explores the profound knowledge inherent in the Mangena Mundhum, a significant genre of Mundhum that encapsulates ancestral memories, migratory journeys, and settlement patterns spanning centuries. As a crucial link to the Yakthung dynasty, Mangena rituals practice connects the Yakthung people to their origins, culture, rituals, belief systems, and worldview. Through this lens, the research seeks to illuminate the ancient history and cultural legacy of the Yakthung lineage. Shaped by power dynamics and vested interests, Nepali historiography often lacks authentic sources, particularly for the prehistoric era. This gap has left scholars reliant on fragmented and uncertain evidence. The study adopts an ethnomethodological approach to address these limitations, integrating exploratory, analytical and ethnographic methods, including literature reviews and firsthand observations of rituals and events. Recognized as a legitimate historical repository, Mangena an ancient oral tradition of the Yakthung community offers invaluable insights into Yakthung prehistory. By analyzing the cultural and historical narratives embedded in Mangena, this research contributes to a deeper understanding of Yakthung heritage and addresses significant gaps in Nepal’s historical record.